Effects of product reviews on purchase intention : online shopping from a presence perspective. - He, Xiaoyu. (2013)
Business-to-consumer (B2C) online retailing is becoming more and more popular among Chinese consumers. With the rise of online fraud, there is an increasing need for consumers to reduce the potential risks with online purchase. Research shows that consumer product reviews (CPRs), as a form of electronic word-of-mouth, can help reduce the risks of online shopping and even influence shoppers’ purchase decisions. However, apart from providing extra information about products, CPRs may have social impact on potential shoppers since they may elicit the presence of the existing customers.